ULTRASOUND AND ITS APPLICATION - Santos De La Cruz, Eulogio (2005)
Ultrasound is used for the non-destructive testing of materials. It is applied to know the inner of a material or components when processing the trajectory of the propagation of sound waves. It is know that propagation of waves inside the piece depends on the discotinuities of the material examined, which allows to evaluate the discontinuity about its form, size, direction, since these offer a resistance known as acoustic impedance. When knowing the propagation of the sound waves, its speed and therefore the property of materials are determined.